Magnetic Continuum Device with Variable Stiffness for Minimally Invasive Surgery - Christophe Chautems; Alice Tonazzini; Quentin Boehler; Seung Hee Jeong; Dario Floreano; Bradley J. Nelson (Advanced Intelligent Systems, 2020)
One of the challenges of minimally invasive surgery is the dexterous manipulation and precise control of small‐diameter continuum surgical instruments. Herein, a magnetic continuum device with variable stiffness (VS) is presented, whose tip is precisely shaped and controlled using an external magnetic field. Based on a low melting point alloy (LMPA), the serial segments composing the continuum device are independently softened via electrical current and remotely deformed under a magnetic torque, whereas the rest of the device is locked in place. The resulting system has the advantage of combining the precision of magnetic navigation with additional degrees of freedom provided by changing the segments stiffness. With a minimum diameter as small as 2.33 mm and an inner working channel, the magnetic continuum device with VS is adapted to use in several therapeutic scenarios, including radio‐frequency cardiac ablations and interventional endoscopy in the gastrointestinal tract. The magnetic torque is used to remotely control the shape of the soft sections, whereas the stiff sections remain unchanged, thus adding degrees of freedom to the magnetic continuum device.